Kemampuan Sains Sederhana Melalui Teknik Bermain Air Pada Anak Kelompok B TK Sinar Jaya Kecamatan Limboto Kabupaten Gorontalo - Meylan Saleh (Magister Pendidikan Nonformal Pascasarjana Universitas Negeri Gorontalo, 2021)
Corresponding author of the preliminary findings that the Sinar Jaya TK ability to interfere with a good color as much as 5 people or 25%, whereas 15 children or 75% do not have the skills interfere with color. Fit these data we need a way to enhance the ability of simple science to children. Many of the strategies, methods and approaches that can be used to enhance the ability of a simple science to child during play, but this use has not shown good results. Therefore in this study the authors sought to find a solution through the method of problem solving techniques of water play. The purpose of this study to enhance the ability of modest science through the engineering group of children playing in the water. The research was conducted in early childhood Sinar Jaya District Limboto Gorontalo district. The subjects in this study is the son of group B, amounting to 20 people, consisting of 14 men and 6 women. Economic background of parents is that there are varied work as farmers, employees, vendors and other work. This study consisted of two cycles and data were analyzed descriptively. Based on the results of the study concluded that the use of color exploration game techniques to improve the ability of science is the cycle I have 5 children, or 25% of children who have the capability of science and in the second cycle there are 18 people or 90% of children who have the capability of science. Thus the cycle I was increasing the number of children who have the capability of science that is of 5 people or 25% to be 18 people or 90% in cycle II. These results means the hypothesis that the action reads if the method of administration tasks with color exploration game techniques applied effectively in the learning of science will be able to enhance the ability of kindergarten children Sinar Jaya group B Limboto Gorontalo district has been proven empirically.